The Influence of E-Service Quality on Repurchase Intention through E-Customer Satisfaction on Shopee Food Application Users in Cirebon City - Siti Amanah; Ramlah Puji Astuti; Soesanty Maulany (Interdisciplinary Social Studies, 2026)
This study aims to analyze the effect of e-service quality on repurchase intention through e-customer satisfaction among Shopee Food app users in Cirebon City. The development of app-based food delivery services encourages companies to improve the quality of their digital services to retain customers and increase user loyalty. This study uses a quantitative approach with the Structural Equation Modeling method based on Partial Least Squares (SEM-PLS) using SmartPLS 4 software. The research data were obtained through online questionnaires distributed to 210 respondents who are Shopee Food users and have used the service at least twice in the last three months. Purposive sampling was applied according to research criteria. The findings indicate that e-service quality has a positive and significant effect on repurchase intention and e-customer satisfaction. Moreover, e-customer satisfaction also shows a positive and significant effect on repurchase intention. The results further reveal that e-customer satisfaction mediates the relationship between e-service quality and repurchase intention. These findings provide practical implications for digital platforms and culinary MSMEs to enhance application usability, service speed, and transaction security to strengthen customer satisfaction and loyalty in the digital economy ecosystem. This study highlights the mediating role of e-customer satisfaction in the relationship between e-service quality and repurchase intention among Shopee Food users in Cirebon City.